Application of a One Health approach to translate policies to action to address priority chemical pollutants: TCDD as an example - Catherine Machalaba; Lauren Cybulska; Fiona Fogarty; Dao Nguyen; Jean Grassman (CABI One Health)
Abstract Pollution is a leading cause of disease burden and deaths globally, with toxic chemicals playing an increasing role. To date, there has been limited focus on a One Health approach for the effective prevention and management of chemical pollution, despite myriad toxicological connections between humans, animals, and the environment. The recent evolution of One Health framing and policy commitments offers an opportunity to examine practical entry points for applying a One Health approach to toxicant risks and impacts. Using the example of the persistent toxicant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), we demonstrate conceptually how a One Health approach can add value to understanding and reducing risk from chemical pollutants, including through the risk analysis cycle. Broader connections are made for monitoring and management of chemical threats, including in relation to the climate and biodiversity crises. The effects of TCDD on humans and other species and ecosystems warrant a holistic approach to evaluate risks and identify and optimize solutions through a multi-sectoral approach. Enhanced impact assessment tools, multi-species literature reviews and field surveys, interagency coordination agreements that formally link global and national organizations with mandates for toxic chemical management and human, animal, and plant health, and cost-benefit analyses employing a One Health economics lens provide practical starting points for making a One Health approach routine when addressing chemical pollution risks and impacts. The One Health Joint Plan of Action, through its Action Track 6, and newly adopted Global Action Plan on Biodiversity and Health offer momentum to build on a new era of tackling chemical pollution to better protect the health of humans, animals, and the environment. One Health impact statement Priority chemical pollutants threaten human, animal, and environmental health, warranting the holistic understanding and coordinated multi-sectoral action enabled through a One Health approach. Noting that the monitoring and management of Persistent Organic Pollutants spans multiple international agreements (e.g., toxic chemicals, food safety, military practices), the overarching global One Health Joint Plan of Action and recently-adopted Global Action Plan for Biodiversity and Health provide key opportunities to take a holistic view in assessing and reducing risks and impacts of pollutants to human health and biodiversity. Using the example of the dioxin TCDD, a persistent organic pollutant, we highlight ways that a One Health approach can be beneficial across the risk analysis cycle to advance policy translation into action.